Penanaman Nilai Beriman Bertakwa kepada Tuhan Yang Maha Esa dan Berakhlak Mulia Profil Pelajar Pancasila Melalui Kegiatan Pembiasaan Siswa di MTs Al-Ma’arif 03 Singosari - A’yun, Qurroti; Indriani,, Sinar Mahardika; Anugrah, Vivian; Amelia, Vernelysa; Khoiri, Muhammad Mirzaq; ., Wahyudi (TABYIN: JURNAL PENDIDIKAN ISLAM, 2022)
This study aims to find out how to optimize the inculcation of the Value of Faith, Fear of God Almighty and Noble Characters of Pancasila Student Profiles through student coaching activities at MTs Al-Ma'arif 03 Singosari. The student habituation activities that are implemented there are the reading of different books and Surahs of the Qur'an and the development of morals and Islamic values every day. In this study using a qualitative research approach. The design used is a case study. While the instruments used as data collection are interviews and observations. The results of field research show that the results of instilling the value of having faith in God Almighty, and having a noble character are the profiles of Pancasila students through habituation activities, namely in the form of faith in God Almighty and having noble character.